Elaboração de farinha de banana pacovan (Musa sapientum schum) desidratada osnoticamente seguida de secagem convencional. - BRITO, Juliana Gomes de. (2016)
This work aimed to study the osmotic dehydration of pacovan banana slices unpeeled banana for flour production at different temperatures osmosis and sucrose concentrations using slices cut to 5 mm thick. The samples were dehydrated in sucrose syrup at concentrations of 40, 50 and 60ºBrix and temperatures of 40, 70ºC, followed by further drying in a heated air dryer at temperatures of 40, 50 and 60ºC. The mathematical models of Lewis, Henderson and Pabis, Page, Peleg and Silva et alii were adjusted to the data of water loss and sucrose gain during osmotic dehydration and to the data of the complementary convective drying, through the LAB Fit Program. After drying, the banana slices with peel were crushed and transformed into flour and analyzed for physical, chemical and physical-chemical analyzes: water content, water activity, pH, acidity in malic acid and microbiological analyzes. The flours were stored in a chamber with controlled temperature at 25ºC for 180 days in laminated packaging and studied for physical, chemical, physical-chemical and microbiological parameters every 30 days. Different cake formulations were prepared with the addition of 0.5% banana flour; 7.5; 10 and 15%, which were optimized and studied in terms of water content, water activity, color, specific mass, specific volume, texture, sensory analysis and microbiological analysis. The selection of formulations took into account the global assessment attributed to the panel of tasters. The results of osmotic dehydration demonstrated that the Peleg model was satisfactory to predict the phenomenon of mass transfer, whereas the models by Page and Silva et alii satisfactorily describe sucrose gain. The description of drying kinetics was best represented by the Page model with values ​​of determination coefficients (R2) greater than 0.9. The analysis of variance of the physical-chemical data of the flours showed that the highest concentrations of osmosis and the highest drying temperatures favored obtaining samples with lower water contents and water activities and higher values ​​of total soluble solids. The incorporation of banana flour influenced the physical characteristics of the cakes, increasing the hardness, guminess, elasticity and chewability and decreasing the stickiness. The content of water, crude protein, fiber and ash increased with the percentage increase of banana flour in the formulations. The results of the characterization of the fresh fruit prove that the banana peels have higher levels of minerals K, Mg, Na, Ca and Mn and fibers than the pulp. The microbiological tests satisfy the microbiological standard for all treated flours and all stored cakes, therefore samples of flours from the temperature of osmosis at 70ºC showed better microbiological stability during storage, at the end of 180 days, the other flours showed high levels of total soluble solids, total titratable acidity, water activity and water content and lower pH and luminosity values. During storage, laminated and bioriented polypropylene packages used in cakes did not prevent water absorption by the samples and influenced the decrease in elasticity.